Risk factors for hepatocellular carcinoma in hepatitis C patients with normal alanine aminotransferase treated with pegylated interferon and ribavirin. Issue 5 (25th August 2013) - Harada, N.; Hiramatsu, N.; Oze, T.; Morishita, N.; Yamada, R.; Hikita, H.; Miyazaki, M.; Yakushijin, T.; Miyagi, T.; Yoshida, Y.; Tatsumi, T.; Kanto, T.; et al.
Summary Pegylated interferon (Peg‐IFN) plus ribavirin combination therapy is effective in patients with hepatitis C virus (HCV) infection and normal alanine aminotransferase levels (NALT). However, it remains unclear whether the risk of hepatocellular carcinoma (HCC) incidence is actually reduced in virological responders. In this study, HCC incidence was examined for 809 patients with NALT (ALT ≤ 40 IU/mL) treated with Peg‐IFN alpha‐2b and ribavirin for a mean observation period of 36.2 ± 16.5 months. The risk factors for HCC incidence were analysed by Kaplan–Meier method and Cox proportional hazards model. On multivariate analysis among NALT patients, the risk of HCC incidence was significantly reduced in patients with sustained virological response (SVR) or relapse compared with those showing nonresponse (NR) (SVR vs NR, hazard ratio (HR): 0.16, P = 0.009, relapse vs NR, HR: 0.11, P = 0.037). Other risk factors were older age (≥65 years vs <60 years, HR: 6.0, P = 0.032, 60–64 vs <60 years, HR: 3.2, P = 0.212) and male gender (HR: 3.9, P = 0.031). Among 176 patients with PNALT (ALT ≤ 30 IU/mL), only one patient developed HCC and no significant risk factors associated with HCC development were found. In conclusion, antiviral therapy for NALT patients with HCV infection can lower the HCC incidence in responders, particularly for aged and male patients. The indication of antiviral therapy for PNALT (ALT ≤ 30 IU/mL) patients should be carefully determined.